(untitled) (Вестник КазНУ. Серия Востоковедения, 2016)
In the present article is considered about phraseology of Japanese language, the specific and types of phraseology of Japanese language. The author researching the phraseology in the Japanese compared with Kazakh one. So she revealed the differences and similarities of the both languages.